Efficacy of Parents’ Involvement in Mathmetics and Psychological Adjustment of students with Hearing Impairment. - Ghunaim, Lama (DIRASAT: EDUCATIONAL SCIENCES, 2016)
This study aimed at investigating the effect of parents involvement in mathmetic achievement and psychological for students with hearing impairment. A total of (54) students with hearing impairment (grades 3,4, and 5) served as a subjects of the study. The subjects were equally divided into two groups; experimental and control. Mathmatic and psychological adjustments tests were administered to the two groups as pre tests. Parents of the experimental group subjects participated in the parent involvement. Program for a period of one semester. The mathmetic and psychological adjustment were administered to the two groups as post – tests. The results of the study revealed that there were significant differences between the experimental and control group in both mathmetics and psychological adjustment in favor of the experimental group prove the effect of parent involvement in their children program.